Study of generation of sinter return fines during transportation. (April 2015) - Harsha Nistala, S.; Sinha, M.; Kumar Choudhary, M.; Bose, G.; Sinha, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Conventional tests of sinter strength such as the Tumbler test and the shatter test cannot predict the effect of transport parameters such as the drop height, conveying length, etc. on the amount of return fines generated during transport. In this work, various steps involved in transportation were simulated using customised drop and vibration tests, and the effect of sinter size, drop height and conveying time on the percentage of return fines and volume breakage was examined. Drop and vibration tests revealed that the extent of volume breakage is higher in case of larger sinter particles, but the percentage of return fines from various size fractions did not follow the corresponding trend in volume breakage. The contribution of various size fractions of sinter to generation of return fines was found to be in the order: 5–10 mm>20–30 mm∼30–40 mm>10–20 mm. For any size fraction, the percentage of fines generated was found to be linearly related to the drop height in the case of drop tests and logarithmically related to the vibration time in the case of vibration tests.